Loss and Genocide in the Archives - Hawkes, Martine, author.
1 online resource
Keywords: "Current official responses to genocide are largely situated within archives of various descriptions - museums, courts, libraries, memoirs and memorials. Through particular readings of the archive, Martine Hawkes examines genocide as it is understood, represented, and responded to. She asks what is expected of the archive - by curators, users and genocide survivors - and considers what role archives play in informing the ethics of how genocide is approached and remembered. This book argues that the archive is constructed and gathered from outside and after the event. The archive, in attempting to contain, comprehend and conclude the event of genocide, betrays a desire to reduce histories to limits, reason and unifiers. Here, the archive privileges a quantitative and definitional reading, engendering a limited and codified response to genocide. In this reading of genocide, much is lost and unknowable. In framing an ethics of approach, six stories, told initially as stand-alone narratives are presented. These accounts then trail recursive loops within the arguments to provide a reminder of the infinite nature of the approach of genocide. This book thus presents the ashes of the event, naming that which eludes and is elided from the archive and archival practice. It sounds a crisis of response to genocide, calling instead for hesitation and uncertainty to inform our otherwise enclosing, limiting, and reductively certain responses."--Provided by publisher.